The Effect of Leadership Style, Work Motivation, and Work Discipline on Employee Performance at Santi Mandala Resort & Spa in Gianyar - I Kadek Agus Ariana; I Made Sumartana; I Gusti Putu Agung Widya Goca (Inisiatif Masyarakat Jurnal Indonesia (IMAJI), 2025)
This research aims to examine the influence of leadership style, work motivation, and work discipline on employee performance at Santi Mandala Resort & Spa, Gianyar. The study employs a quantitative approach with a saturated sampling technique involving 50 employees. Data were collected through questionnaires and analyzed using multiple linear regression. The findings indicate that leadership style, work motivation, and work discipline simultaneously and significantly affect employee performance. Partially, each variable also shows a positive and significant effect on performance. The results suggest that effective leadership, motivational strategies, and disciplined work behavior play crucial roles in improving employee productivity and organizational success within the hospitality industry.